Mechanisms of haplotype divergence at the RGA08 nucleotide-binding leucine-rich repeat gene locus in wild banana (Musa balbisiana) - Baurens, Franc-Christophe (BioMed Central, 2010)
BACKGROUND: Comparative sequence analysis of complex loci such as resistance gene analog clusters allows estimating the degree of sequence conservation and mechanisms of divergence at the intraspecies level. In banana (Musa sp.), two diploid wild species Musa acuminata (A genome) and Musa balbisiana (B genome) contribute to the polyploid genome of many cultivars. The M. balbisiana species is associated with vigour and tolerance to pests and disease and little is known on the genome structure and haplotype diversity within this species. Here, we compare two genomic sequences of 253 and 223 kb corresponding to two haplotypes of the RGA08 resistance gene analog locus in M. balbisiana "Pisang Klutuk Wulung" (PKW). RESULTS: Sequence comparison revealed two regions of contrasting features. The first is a highly colinear gene-rich region where the two haplotypes diverge only by single nucleotide polymorphisms and two repetitive element insertions. The second corresponds to a large cluster of RGA08 genes, with 13 and 18 predicted RGA genes and pseudogenes spread over 131 and 152 kb respectively on each haplotype. The RGA08 cluster is enriched in repetitive element insertions, in duplicated non-coding intergenic sequences including low complexity regions and shows structural variations between haplotypes. Although some allelic relationships are retained, a large diversity of RGA08 genes occurs in this single M. balbisiana genotype, with several RGA08 paralogs specific to each haplotype. The RGA08 gene family has evolved by mechanisms of unequal recombination, intragenic sequence exchange and diversifying selection. An unequal recombination event taking place between duplicated non-coding intergenic sequences resulted in a different RGA08 gene content between haplotypes pointing out the role of such duplicated regions in the evolution of RGA clusters. Based on the synonymous substitution rate in coding sequences, we estimated a 1 million year divergence time for these M. balbisiana haplotypes. CONCLUSIONS: A large RGA08 gene cluster identified in wild banana corresponds to a highly variable genomic region between haplotypes surrounded by conserved flanking regions. High level of sequence identity (70 to 99%) of the genic and intergenic regions suggests a recent and rapid evolution of this cluster in M. balbisiana.